Sistem Informasi Penjualan Emas Pada Perusahaan Modern Investasi Berbasis Website - Wahyudi, Wiwit; Baikhaqi, Nurul (MEANS (Media Informasi Analisa dan Sistem), 2022)
Computers provide the right solution in producing the most recent information. As is the case in every company, both government-owned and private companies have a relatively large number of transactions, so a database is needed that can store and process the data efficiently, quickly and can be used whenever needed.Modern Investments located at Jl. Raya Sekopek Plantaran, Kaliwungu is a gold bullion investment company that is very strategic and feasible to facilitate future economic changes to be better or more prosperous than before.In carrying out Modern Investments, employees process data from storage and installment payments still using a program that is still simple, and the marketing party records books for making prospective members, member installments and bookkeeping records in a ledger and then entered into the program.Based on the problems that exist in Modern Investments, the author wants to propose a sales administration application system design to be taken into consideration in helping speed up the process of recording cash and credit sales transactions and can provide the information needed Modern Investments in the form of member reports, cash sales reports, credit sales reports , and installment reports, the sales information system design using the web.Making this application is expected to be one of the efforts that can be made to overcome problems that often occur so that it can increase work effectiveness which of course will have an effect on improving the quality of service to customers.